How do you solve y= -2x + 2 and 6x + 2y = 3?

1 Answer
Jun 18, 2018

Answer:

#(x,y)=(-1/2,3)#

Explanation:

Given
[1]#color(white)("XXX")y=-2x+2#
[2]#color(white)("XXX")6x+2y=3#

The form given for equation [1] makes solution by substitution the most obvious method:

Base on [1] we can substitute #(-2x+2)# for #y# in [2]
[3]#color(white)("XXX")6x+2(-2x+2)=3#

Simplifying [3]
[4]#color(white)("XXX")2x+4=3#
or
[5]#color(white)("XXX")x=-1/2#

We can now substitute #(-1/2)# for #x# in [1]
[6]#color(white)("XXX")y=-2(-1/2)+2=3#